(untitled) (Journal of Humanitarian and Applied Sciences, 2019)
The (1E,4E)-1,5-bis (4-nitrophenyl) penta-1,4-dien-3-one (3) was synthesized by treatment of acetone with 4-nitrobenzaldehyde using 1:2 mol. respectively in the presence of basic medium of sodium hydroxide in a good yield. The structure of the prepared compound was characterized by elemental analysis, IR,1H-NMR, and mass spectra. The newly prepared compound was screened for the antibacterial activity against Escherichia coli (G-) and Staphylococcus aureus (G+) bacterial strains by the disc diffusion method, and for their antifungal activity against Aspergillus flavus and Candida albicans in N,N-dimethylformamide by the agar diffusion method. The results of the test compound exhibited low cadre of antibacterial and antifungal activities compared with the standard drug Amikacin, therefore, minimum bactericidal concentration (MBC) and minimum fungicidal concentration (MFC) were not determined for the test compound.